THE USE OF TEACHERS’ QUESTIONING STRATEGIES TO STIMULATE STUDENTS’ CRITICAL LITERACY: A CASE OF TWO ENGLISH LECTURERS IN INDONESIA - Siti Aimah; Bambang Purwanto (Indonesian EFL Journal, 2019)
To create an effective teaching, teachers should consider the use of questioning strategies to not only elicit students’ attention, but also stimulate their critical literacy. This study aims to know the use of questioning strategies used by the English lecturers in the classrooms. An in-depth research was done to provide the information dealing with the reasons of using the questioning strategies and the questioning strategies used to stimulate students’ critical literacy. A case study was carried out by involving two English lecturers of Universitas Muhammadiyah Semarang, Indonesia. Both of them taught the second semester students in Reading class and Language Testing class in the Academic Year of 2017/2018. Data were collected through video-recordings and interview with both lecturers. The findings showed that both lecturers used question-planning strategies and question-controlling strategies as proposed by Xuerong (2012) and Walsh (2011). To stimulate the students’ critical literacy, open-referential questions and follow-up questions were posed to encourage them to be more critical. Wait-time given by the lecturers also helped the students answered the questions, and their questions were more accurate, elaborate, and reasonable.Keywords: critical literacy; effective teaching; question-controlling strategies; question-planning strategies; teachers questioning strategies.